Um método para o alinhamento entre modelos de processos e modelos objetivos baseados de contribuição - Reis, Ariane Nunes (2013)
Contemporary organizations have been using process modeling to formalize their business processes so that they can be properly followed, monitored and automated by the organizational members. More recently, there is also a growing interest in the alignment between business process models and goals models, since this alignment accounts for an explanation of how goals are operationalized in terms business process and how the organization works with the aim of achieving its objectives and strategies. Although this recognition, methods that support the systematic alignment between process models and goals models are still scarce. In order to contribute in this regard, this dissertation presents the proposal of the Method for Alignment of Processes Models and Goals Models based on contribution analysis (in Portuguese: Método para Alinhamento entre Modelos de Processos e de Objetivos baseado em análise de contribuição - MAPO), proposing well-defined steps to guide the analyst in identification of inconsistencies between business process models and their corresponding goals models. In order to support this alignment, this work builds its contribution on previous work regarding the classification of objectives and analysis of traceability in meeting goals. This dissertation describes an empirical study conducted to validate the feasibility of the method and to collect suggestions for improvements. Both to illustrate as well as to validate, we use real case studies, thus providing a realistic context for the application of the method. The validation results are promising and also bring important suggestions, which led to the proposal of a new version of the method which is also documented in this dissertation.